PU-type-dependent reference frame selection method for HEVC. Issue 1 (January 2017) - Hong, Seungbeom; Yang, Dongjun; Park, Byungkil; Kim, Hyungwook; Yu, Sungwook
Abstract This paper proposes an efficient reference frame selection method for HEVC. The proposed method makes use of the correlation between the best reference frame (BRF) in the $$2N× 2N$$ 2 N × 2 N prediction unit (PU) and the BRFs in the other types of PUs. By efficiently using the BRF information of the $$2N× 2N$$ 2 N × 2 N PU, the proposed method significantly reduces the number of reference frames to be examined. To minimize the performance degradation, the proposed method changes the examination order of the inter-prediction modes and makes use of the best merge mode information. It also uses the rate-distortion cost information of the $$2N× 2N$$ 2 N × 2 N PU so as not to skip important reference frames. Because the proposed method deals with both uni-prediction and bi-prediction, it can be efficiently used, not only for LP but also for LB and RA coding structures. As a result, the proposed method reduces the encoding time by 12.7, 16.4 and 5.6 % with only 0.26, 0.29 and 0.04 % BD-BR increase for the LP, LB and RA coding structures, respectively.